The giraffe and the pelly and me - Dahl, Roald; Blake, Quentin (New York, N.Y Puffin Books, 1998)
A small boy with a desire to own a candy shop meets a window-washing team composed of a giraffe, a pelican, and a monkey and together they go to work for the wealthy Duke of Hampshire, who makes all their dreams come true
English stories
For children from 7 to 10 years old
Keywords: Candy -- Fiction; English stories; Giraffe -- Fiction; Monkeys -- Fiction; Pelicans -- Fiction